Os princípios do Equador no Brasil: o caso da Usina Hidrelétrica de Santo Antônio - Modesto, Raíssa Barbosa Moura (2011)
The objective of this research is to verify the implementation of the Equator Principles in Brazil and the Madeira River Complex project, considering only the Santo Antonio Plant. First, we discuss the concept of the Equator Principles; the institutions that developed them; their certification mechanism. It describes its evolution in Brazil, its validity as a tool to mitigate the financial risks of banks and, finally, why Brazilian banks have joined this initiative. Subsequently, we will discuss the energy sector, contextualizing the scenario and the trade-off between power generation and environment. We will do a historical of the Madeira River Complex project, specifically the Santo Antonio Plant, where it is located. Furthermore, we will present the potential benefits and costs in Brazilian economy. Finally, we will make an assessment of the Santo Antonio Plant of the light of the Equator Principles, in other words, we will relate the principles with the plant and its potential economic, social and environmental impacts, both for financial institutions, as for Brazilian society